Chronic stress in fish: Investigation of the cellular response to persistent environmental hypercapnia and malnutrition in two marine fish species, turbot (Psetta maxima) and cod (Gadus morhua) via RT-qPCR - Hermann, Bernd Timo (2018)
For finfish, coping with stress is not only relevant in the context of ecology but has also garnered lots of attention with respect to animal welfare in aquaculture. Yet, In particular the response to chronic stress still raises many questions regarding regulatory dynamics and mechanisms. I investigated the impact of two chronic stressors, relevant for aquaculture and ecology (hypercapnia and malnutrition), in two fish species, turbot (Psetta maxima) and Atlantic cod (Gadus morhua) via gene expression analysis. The aim of this study was to gain new insights in the respective coping mechanisms and detect potential communalities. Further, results were also screened for putative biomarkers for the detection and monitoring of environmental and culture induced stress. In each experiment, data pointed to divergent changes in gene expression between treatment levels, indicating different coping strategies dependent on the respective stress intensity. Further, my findings implied overall changes in lipid- and fatty acid metabolism as general part of the cellular response to chronic stress. Hints for additional hypoxia-like effects, reduced metabolic activity and increasing oxidative stress varied between the experiments, but seemed to increase parallel to the severity of the stressor. Several cues suggested that especially reactive oxygen species may play a central role in mediating both, regulation of gene expression and detrimental consequences of chronic stress. These findings provide new insights in the cellular response to chronic stress in fish and could help to improve contemporary stress and welfare concepts. The regulatory and damaging effects of reactive oxygen species provide a mechanistic explanation for divergent gene expression patterns and may also explain wear and tear like effects. Finally, I was able to identify multiple genes, which can be utilized as stress biomarkers in future studies. Für Fische ist die Bewältigung von Stress nicht nur im ökologischen Kontext, sondern auch in Hinblick auf ...